The effect of earnings management and price to book value on stock returns at PT Sampoerna Agro Tbk for the Period 2013 – 2023 - Rahmawati, Alya; Irnawati, Jeni (Journal of Economics and Business Letters, 2024)
This research aims to determine the influence of Profit Management and Price to Book Value (PBV) variables on stock returns at PT Sampoerna Agro Tbk. This type of research is quantitative. The data analysis technique used is panel data regression with an 11 (eleven) year time series, namely the 2013-2023 period and 1 (one) company. Based on the results of the partial test (T test) for Profit Management, the T value obtained is 0.846 with a significance of 0.420. Because Tcount < Ttable (0.846 < 2.262) and the significance value < significant level (0.420 > 0.05). So the conclusion is that Earnings Management has no effect and is not significant on Stock Returns. The research results for Price to Book Value (PBV), obtained a T value of 1.005 with a significance of 0.341. Because Tcount < Ttable (1.005 < 2.262) and the significance value < significant level (0.341 > 0.05). So the conclusion is that Price to Book Value (PBV) has no positive effect on Stock Returns. The results of simultaneous hypothesis testing (F test) can be seen that the Fcount value is 0.956 which is smaller than Ftable of 4.46 or 0.956 <4.46 as for the significance value amounting to 0.424 is greater than 0.05 or 0.424 > 0.05, so it can be concluded that Earnings Management and Price to Book Value simultaneously do not have a significant effect on Stock Returns.